Analysis of Mobile Phones in Digital Forensics - Dogan, Sengul; Akbal, Erhan (Ieee, 2017)
Nowadays, the need to tackle rapidly increased crimes is increasing day by day to help ensuring justice. Digital forensics can be defined as the process of collecting, examining, analyzing and reporting of digital evidence without any damage. Digital forensics requires a detailed examination of devices such as computers, mobile phones, sim cards, tablets that contain digital evidence regardless of whether the crime is large or small. Among these devices, mobile phones take an important place in digital forensics because of their widely usages by every individual. The importance of examining of the data called as evidence in mobile phones has increased with advances in technology, operation capacity, storage capacity and functionality. In a forensics case, mobile phones must be examined by authorized persons and the data obtained from the device must be brought to standards that can be used forensically. In this study, examination and analysis of mobile phones in terms of digital forensics is evaluated. At the same time, data that can be obtained from mobile phones through a sample application has been investigated.
40th International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO) -- MAY 22-26, 2017 -- Opatija, CROATIA
Keywords: Mobile Phone; Digital Evidence; Digital Forensics